Pengaruh Lingkungan terhadap Pengembangan Bahasa pada Anak - Yenni Atikah; Syamsiah Depalina (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
This study examines the influence of family, social, and educational environments on children's language development. The purpose of this study is to understand how interactions in these three environments affect language skills. The method used is a qualitative approach with data collection through in-depth interviews and observations at home, school, and the social environment. The results of the study indicate that family support, positive interactions with peers, and effective teaching methods at school significantly improve children's language skills. The conclusion of this study emphasizes the importance of creating a supportive environment in all aspects to facilitate optimal language development.